A Locus for Autosomal Recessive Pseudoxanthoma Elasticum, with Penetrance of Vascular Symptoms in Carriers, Maps to Chromosome 16p13.1 - van Soest, Simone; Swart, Jaap; Tijmes, Nel; Sandkuijl, Lodewijk A.; Rommers, Jago; Bergen, Arthur A.B.

(untitled) (Genome Research, 1997)
Pseudoxanthoma elasticum (PXE) is a heritable systemic disorder characterized by calcification of the elastic fibers of the connective tissue. Symptoms are predominantly noted in the eye, the skin, and the cardiovascular system, resulting in visual loss, skin lesions, and life-threatening vascular disease. In this study we combined homozygosity mapping and genome scanning with 374 markers in affected individuals from a PXE family from a genetically isolated population in The Netherlands. Initial homozygosity in two or three patients was found with up to 20 markers, among which D16S292 located in 16p13.1. Upon refined and more extensive family screening of the latter region, close linkage without recombination was found with the marker D16S764 (Z max = 6.27). Despite clear autosomal recessive inheritance of the ocular symptoms in PXE, vascular symptoms appear in 40%–50% of the heterozygotes.